Diseño e implementación del sistema de control para mesa de cirugías de operación electrohidráulica DT-12B en el Laboratorio de Biomédica de la Universidad Antonio Nariño sede Cartagena (2023)
This research project deals with the design and implementation of a control system to activate the different actuators that generate the movements of the DT-12B surgical table of the Biomedical laboratory located in the facilities of the Antonio Nariño University, Cartagena, this project arises from the need to have functional equipment that could not be used due to damage to the control system cards. The present work describes the design process of the electronic cards of the control system to energize the hydraulic pump (120VAC) and energize the solenoids (24VDC) of the valve body of the electro-hydraulic movement system implemented in the table. The elements used to carry out this control system are the PIC16F628A microcontroller accompanied by other components such as optocouplers, Arduino RF transmission and reception modules, current drivers, thyristors, among others. The realization of these electronic cards with the selected elements replaces the previous control card, providing new technologies, the possibility of changing the programming and sequence of movements, improving the control capacity over the electro-hydraulic system.